2023
DOI: 10.1186/s12879-023-08017-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extended spectrum beta lactamase and molecular detection of blaTEM, blaSHV and blaCTX-M genotypes among Gram negative bacilli isolates from pediatric patient population in Gaza strip

Abstract: Background Extended-spectrum β lactamases (ESBLs), have the ability to hydrolyze and cause resistance to various types of the β-lactam antibiotics, including the extended-spectrum (or third-generation) cephalosporins (e.g., cefotaxime, ceftriaxone, ceftazidime) and monobactams (e.g., aztreonam). ESBL-producing Gram negative bacteria is still posing significant therapeutic challenges. Objectives To assess the prevalence and molecular characteristic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
(51 reference statements)
2
9
0
Order By: Relevance
“…ESβLs are responsible for the increasing bacterial pathogens hydrolysing activity by enabling the breakdown of the β-lactam ring, thereby inactivating the antibiotic. Similar findings have been documented in recent related studies by [ 27 ] on how the ability to hydrolyse antibiotics by ESβL genes is causing significant resistance to various β-lactam antibiotics [ 28, 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…ESβLs are responsible for the increasing bacterial pathogens hydrolysing activity by enabling the breakdown of the β-lactam ring, thereby inactivating the antibiotic. Similar findings have been documented in recent related studies by [ 27 ] on how the ability to hydrolyse antibiotics by ESβL genes is causing significant resistance to various β-lactam antibiotics [ 28, 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar studies reported that the ESBL producer frequency reached 82.5% and 41.1% in patients from India [ 17 , 18 ], 55.5% from Saudi Arabia [ 19 ], 66.56% from Nepal [ 20 ], 58% from Vietnam [ 21 ], 42% from Southwestern Iran [ 22 ], 48% from Pakistan [ 23 ], and 55.3% from Palestine [ 24 ].…”
Section: Discussionmentioning
confidence: 68%
“…Studies have shown that E. coli is the major cause of diarrhea [99][100][101][102]. Despite the presence of various bacterial species in the human gut, E. coli is more resistant to antibiotics than other Enterobacteriaceae [103,104]. Therefore, antibiotic-resistant strains of E. coli present a significant challenge in the global fight against infectious diseases.…”
Section: Discussionmentioning
confidence: 99%